Analisa Efisiensi Relatif Pada PT Bank Syariah X Periode 2018 - Fajar, Akhmad; Fitrijanti, Tettet; Sukmadilaga, Citra (Program Studi Akuntansi FPEB UPI, 2020)
PT. BSX is the largest Islamic banking in Indonesia. Total assets of 92 trillion in August 2018 and the targets in 2020 are 200 trillion assets. In order to achieve the targets, PT. BSX must improve its overall performance. The performance of a bank can be assessed based on its productivity and by calculating the input and output ratios in order to obtain the relative efficiency measurement. This study aims to determine the level of relative efficiency. This study discusses how the efficiency of branch offices in PT.BSX, this study analyzed 91 branch offices out of 518 branch and sub-branch offices. Data Envelopment Analysis (DEA) was used with analysis units that have full authority or a Decision Making Uni PT BSX. The results of this study shows that the average relative efficiency from January 2018 to August 2018 is 23.6 branch and sub-branch offices, and the highest relative efficiency is 28 branch and sub-branch offices in February 2018 and July 2018. Results of this study are expected to provide information on how the strategies used by branch offices to maintain the level of relative efficiency.Abstrak. PT. BSX merupakan perbankan syariah terbesar di Indonesia dengan total aset sebesar 92 triliun pada Agustus 2018 dan ditargetkan pada 2020 mencapai 200 triliun pada 2020. Oleh sebab itu, seluruh kinerja PT. BSX harus ditingkatkan. Kinerja sebuah bank dapat dinilai dari produktivitas dengan menghitung rasio input dan output sehingga didapatkan ukuran efisiensi relative. Penelitian ini bertujuan untuk mengetahui tingkat efisiensi relative PT. BSX. Penelitian ini menganalisa 91 kantor cabang dari total 518 kantor cabang dan kantor cabang pembantu. Teknik analisis yang digunakan adalah Data Envelopment Analysis (DEA). Penelitian ini membahas mengenai bagaimana tingkat efisiensi kantor cabang yang ada di PT.BSX, hasil penelitian ini menunjukan bahwa efisiensi relatif rata – rata dari mulai bulan Januari 2018 sampai dengan Agustus 2018 sebesar 23.6 kantor cabang dan kantor cabang pembantu, dengan jumlah paling banyak sebesar 28 kantor cabang dan kantor cabang pembantu pada bulan Februari 2018 dan Juli 2018. Hasil penelitian ini diharapkan memberikan informasi mengenai bagaimana strategi yang digunakan oleh kantor cabang untuk menjaga tingkat efiesiensi relatif.